2021
DOI: 10.3390/pharmaceutics13111831
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of In Vitro and In Silico Methods for Aerodynamic Characterization of Powders for Inhalation

Abstract: In vitro assessment of dry powders for inhalation (DPIs) aerodynamic performance is an inevitable test in DPI development. However, contemporary trends in drug development also implicate the use of in silico methods, e.g., computational fluid dynamics (CFD) coupled with discrete phase modeling (DPM). The aim of this study was to compare the designed CFD-DPM outcomes with the results of three in vitro methods for aerodynamic assessment of solid lipid microparticle DPIs. The model was able to simulate particle-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It can be concluded that the DPI device considered in this study has a lower percentage of total deposited particles (higher efficiency) than the devices from the literature at an airflow rate of 60 l/min. In addition, the in vitro results presented in [25] showed a 13-17% particle deposition for the same DPI formulation, meaning that the results from the CFD-DPM simulations correspond well to the in vitro results. In relation to the definition of particle behavior as a result of drag and adhesion moment values, Figure 9 shows the drag and adhesion moment values for the same particle ID for COR_normal = 0.75 and COR_tangential = 0.75.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…It can be concluded that the DPI device considered in this study has a lower percentage of total deposited particles (higher efficiency) than the devices from the literature at an airflow rate of 60 l/min. In addition, the in vitro results presented in [25] showed a 13-17% particle deposition for the same DPI formulation, meaning that the results from the CFD-DPM simulations correspond well to the in vitro results. In relation to the definition of particle behavior as a result of drag and adhesion moment values, Figure 9 shows the drag and adhesion moment values for the same particle ID for COR_normal = 0.75 and COR_tangential = 0.75.…”
Section: Resultssupporting
confidence: 64%
“…Although several papers [9,13,20] investigated the behavior of particles inside the DPIs and particle wall collision, there are no published studies investigating whether a particle rebounds after impacting a wall. Our previous publication [25] compares in vitro and in silico methods for DPI aerodynamic characterization, with the goal of comparing the results of the CFD-DPM simulations with the results of three in vitro methods for the DPI aerodynamic assessment of solid lipid microparticles. In the current study, we focus on the development of CFD-DPM methods to investigate the particle detachment process (sliding and rolling), including the fluid dynamic interaction between the flow and the particles stuck to the wall, by defining equations to describe the sticking and rebounding (sliding and rolling) mechanisms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained here were in accordance with the patterns identified by the in vitro measurements. However, the in silico models can show lower lung deposition values compared to the in vitro methods (i.e., ACI) [ 55 ]. The high extra-thoracic (ET), upper airways, and deposition results here were due to the shorter inhalation time used (2.04 s), which is half the inhalation time that was used in ACI.…”
Section: Resultsmentioning
confidence: 99%
“…By conducting this test, the uniformity and spread of the spray could be visually examined and analysed for consistency and effectiveness. 24 …”
Section: Methodsmentioning
confidence: 99%